Fostering construction firm resilience through persuasive narratives of strategy: a conceptual framework - Zungu, Zamageda; Laryea, Samuel; Nkado, Raymond (University of the Witwatersrand, Johannesburg, 2024)
Amid macroeconomic, political, environmental and technological disruptions that have previously led to the failure of contracting firms, the construction industry faces the imperative to foster organisational resilience. While contemporary literature proposes diverse strategies to manage these disruptions effectively, it lacks clarity on how these strategies are conceptualised and practically mobilised within contracting organisations. However, a notable deficiency of the literature is that the manner in which these strategies are conceptualised and mobilised persuasively within contracting organisations remain unidentified. This study fills this void by conducting a comprehensive literature review, proposing a conceptual framework on the persuasive mobilisation of organisational resilience strategies within the construction sector. Through the lens of the strategy-as-practice perspective and drawing upon theoretical insights from narrative theory, this research intricately examines the interplay between contextual factors such as industry dynamics, organisational resilience strategies, narrative building blocks, strategic discourse and narrative persuasion. Specifically, this study underscores the significance of narrative infrastructure as the contextual canvas upon which strategic narratives are crafted and enacted. By elucidating the impact of narrative infrastructure on organisational actions and member perceptions, this framework not only advances theoretical understanding but also offers actionable insights for enhancing organisational resilience through strategic narratives. This research contributes to both academia and industry by shedding light on the pivotal role of narrative infrastructure in construction firms and providing pragmatic pathways for leveraging it effectively.
This paper was presented at the Proceedings of the WABER SuDBE 2024 Conference, 30th – 31st July 2024, University of the Witwatersrand, Johannesburg, South Africa.
Keywords: Construction firms; Narrative infrastructure; Narrative persuasion; Organisational resilience strategies; Strategy-as-practice; SDG-8: Decent work and economic growth